Femoral and tibial cementless fixation neither increases blood loss nor impedes early functional recovery: A randomized controlled trial - Cao, Jian; Liao, Kai; Li, Ze-xi; Wang, Duan; Chen, Jia-li; Wang, Hao-yang; Zhou, Zong-ke (Frontiers in Surgery, 2023)
Background Whether cementless fixation on femoral and tibial components increases blood loss during total knee arthroplasty (TKA) is unclear. The purpose of this randomized controlled trial was to compare blood loss and early functional recovery between patients who underwent cementless or cemented TKA. Methods Between November 2021 and April 2022, sixty-one eligible patients at our medical center were randomized to cementless and cemented group. The primary outcome was total blood loss (TBL). Secondary outcomes were drainage, knee swelling, anemia, transfusion, hematological indicators, early functional recovery, and postoperative complications. The early functional recovery included range of motion (ROM), Hospital for Special Surgery (HSS) score, walking distance. Results A total of 61 patients were analyzed, of whom 30 underwent cementless fixation. On postoperative day 1, the mean TBL was 394.39 ml (SD 182.97 ml) in the cementless group and 382.41 ml (SD 208.67 ml) in the cemented group (P = 0.863). By postoperative day 3, the corresponding mean TBL was higher at 593.48 ml (SD 230.04 ml) and 603.80 ml (SD 213.16 ml) (P = 0.751). The two groups did not differ significantly in drainage, knee swelling, anemia, levels of hemoglobin or hematocrit or platelets, ROM, HSS score, walking distance, or rates of transfusion or postoperative complications. Conclusions Cementless fixation on femoral and tibial components during TKA does not increase blood loss or impede early functional recovery, which suggests that clinicians need not worry about blood loss and early functional recovery when deciding what type of fixation to perform during TKA. Trial registration Number: ChiCTR2100052857; Date: November 6, 2021.